The Influence Of Consumer Ethnocentrism, Attitudes And Consumer Intentions On Actual Purchasing Behavior On Instant Noodle Products - Fatrisia, Mixilia Embun; Witjaksono, Beny; Yudistria, Yuyus; Baskara, Ika (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
Consumer ethnocentrism is very important because it affects consumer purchasing decisions. This study aims to reveal how demographic factors such as age, gender, education, and income affect consumers' views on domestically made instant noodles and foreign-made instant noodles which affect attitudes, intentions, and purchasing behavior. This study uses a purposive sampling method involving 200 consumers who consume domestically made instant noodle products and foreign-made instant noodle products in the JABODETABEK area. The results of primary data analysis were carried out using the Structural Equation Modeling (SEM) method. The sample criteria are consumers who consume domestically made instant noodle products and instant noodle products made abroad at least 2 times. The results showed that consumer demographics affect consumer ethnocentrism, consumer ethnocentrism affects consumer attitudes, consumer attitudes affect consumer intentions, consumer ethnocentrism has no effect on consumer intentions, consumer intentions affect actual purchasing behavior. This study contributes that age, income and ethnocentrism significantly influence consumer attitudes and intentions towards local products and it is recommended that the sample be expanded and additional factors that may influence the relationship between ethnocentrism, consumer attitudes and purchase intentions be taken into account. Further research could also examine the long-term impact of ethnocentrism on actual purchase behavior as well as other factors that could potentially influence consumer decisions in greater depth. Keywords: Consumer demographics, Consumer ethnocentrism, Attitudes, Consumer intentions and Actual purchase behavior